A study on type of emergencies brought to C. U. Shah Medical College and Hospital by 108 and awareness regarding the services in the general population of Surendranagar, Gujarat - Joshi, Jwalant B.; Jadeja, Yadeepsinh M.; Jasani, Pratik K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Emergency response service (ERS) is associated with medical, police emergency and fire. In the Indian context, a much discussed and successful public-private partnership (PPP) model for ERS is the 108 emergency service being managed and operationalized by EMRI. The World Health Organization has projected that by 2020 road crashes will be a major killer in India. It is a well-accepted fact that a patient who receives basic care from trained professionals and transported to the nearest healthcare facility within 15-20 minutes of an emergency has the greatest chance of survival and terms like ‘The Golden Hour’ and the ‘Platinum Ten Minutes’ that imply the importance of it. Methods: A cross sectional study was carried out in Surendranagar district. Out of 10 talukas of district 4 talukas were selected randomly; out of them one village was selected from each taluka. 20 houses were selected randomly from each village; one adult male and one adult female from selected house were included for the study. Results: 100% respondents knew that 108 could be used for medical emergencies where as 3.57% and 6.43% of respondents, respectively, knew that it also could be used for police and fire type of emergencies. Awareness regarding ‘108’ services and literacy status of respondents showed statistically significant association. Conclusions: Although people were aware about ‘108’ service and had faith in the service, there is large gap in knowledge as to how and when to utilize it including police and fire emergencies.